THERMAL PERFORMANCE OF AVIARY PROTOTYPES FITTED WITH OSB PANEL CEILING MADE OF BALSA WOOD WASTES - Barbirato, G. H. A.; Lopes Junior, W. E.; Oliveira, D. C. G.; Nagata, E. Y.; Caneppele, F. L.; Fiorelli, J. (Revista Brasileira de Engenharia de Biossistemas, 2019)
This study describes the potential of using an OSB panel ceiling, made of Balsa wood wastes agglomerated with a polyurethane resin based on castor oil, in prototypes of aviaries covered with fiber cement tiles. For the study, the internal temperature, relative humidity and the thermal comfort indexes, such as the environmental thermal index of productivity for broilers (IAPfc) and enthalpy, were measured and a Fuzzy logic classification system was used. The data were collected during the spring and summer, for 15 days. The results indicate that the presence of ceiling provided a reduction in the radiation transfer to the interior of the aviary prototypes, reflecting on the reduction of the ambient temperature and the thermal comfort indexes measured during spring and summer. Based on the Fuzzy classification system and on the data obtained, it can be concluded that there is a small difference between the aviaries with and without a ceiling.